Rancang Bangun Jaringan Berbasis Mikrotik Di Kp. Mulyasari, Desa Sukamulya, Kabupaten Bogor - Muhammad Fachru Rizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The need for communication and accessing information easily is very necessary. Kp. Mulyasari is in a place where there is no signal (Blank spot) so that communication is hampered. With this background, the goal is to help the people of Kp. Mulyasari be able to connect to the internet to make it easier to communicate and get information. The method used is the substitution of science and technology by offering more modern science and technology and mediation by becoming a mediator for the local community. The expected result is that the procurement of this network can make it easier for the public to access information, especially about agriculture.